Civilian Exclusion Order No.1. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows military police posting Civilian Exclusion order no. 1, affecting Japanese living in Bainbridge Island, in Puget Sound, Washington.